2022
DOI: 10.1039/d2tc02952a
|View full text |Cite
|
Sign up to set email alerts
|

A-site deficiency improved the thermoelectric performance of high-entropy perovskite manganite-based ceramics

Abstract: Perovskite-type manganite-based ceramics is a promising thermoelectric material at high temperature, while the poor electrical resistivity and thermal conductivity restrict the application in area of thermoelectricity generators. Entropy engineering can...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…The small polaron hopping conduction plays an important role in material systems with large effective masses and strong carrier–lattice interactions . The activation energy can be determined over the entire temperature range using the equation: ρ = ( T / A ) .25em exp ( E a k B T ) where k B is the Boltzmann constant and A is the pre-exponential term related to the scattering mechanism, defined as A = n e 2 a 2 ϑ 0 ( 1 c ) / k where n , e , a , ϑ 0 , and c represent carrier concentration, electron charge, intersite distance of hopping, optical phonon frequency, and the fraction of sites containing electron. Figure b shows the resistivity and material constants for all samples, as summarized in Table .…”
Section: Resultsmentioning
confidence: 99%
“…The small polaron hopping conduction plays an important role in material systems with large effective masses and strong carrier–lattice interactions . The activation energy can be determined over the entire temperature range using the equation: ρ = ( T / A ) .25em exp ( E a k B T ) where k B is the Boltzmann constant and A is the pre-exponential term related to the scattering mechanism, defined as A = n e 2 a 2 ϑ 0 ( 1 c ) / k where n , e , a , ϑ 0 , and c represent carrier concentration, electron charge, intersite distance of hopping, optical phonon frequency, and the fraction of sites containing electron. Figure b shows the resistivity and material constants for all samples, as summarized in Table .…”
Section: Resultsmentioning
confidence: 99%
“…From this work, it is revealed that PbXO 3 could be the next potential TE material which can be operated even at a very high temperature. However, more rigorous work is needed in relation to the transport coefficients to increase the TE efficiency either by high-entropy engineering which was already done to improve the TE performance on perovskite manganite-based ceramics such that these compounds can be used as practical TE devices …”
Section: Resultsmentioning
confidence: 99%
“…The achieved α of −370 μV K −1 at 1150 K and the impressively low k of 0.8 W W m −1 K −1 at 330 K give rise to ZT of 0.23 at 1150 K. This value is currently the highest observed among TEMs based on rare-earth-free HEOs with a tungsten bronze-type structure. Shi et al 200 applied the entropy-driven concept on the perovskite-type manganite structure RE 0.2 Ca 0.2 Sr 0.2 Ba 0.2 Y 0.2 MnO 3 (where RE = La, Nd, Ho, and Lu). The achieved total k is very low 0.94 W m −1 K −1 at 1073 K for Lu 0.2 Ca 0.2 Sr 0.2 Ba 0.2 Y 0.2 MnO 3 .…”
Section: Overview Of High-entropy Thermoelectric Materialsmentioning
confidence: 99%